2001
DOI: 10.1080/00986440108912883
|View full text |Cite
|
Sign up to set email alerts
|

Airside Performance of Staggered Tube Bundle Having Shallow Tube Rows

Abstract: Clum. Ens. C m . . 2Rll. Val. 187. pp. 129-147 Rcprinu available dinrrly from the publisher Photocopying pcrmittd by license only Q 2001 OPA (Ovcrwrr Publirhcrl A m i s t i o n ) N.V. Published by lianse undcr the Gordon and B m c h Scicnoc Publirhcn imprint.Airside performance for tube bank having N= 1-6 are reported in this study. Test results indicated that the heat transfer coefficients for N = l and N = 2 are comparable and the heat transfer coefficients increase with the number of tube row. For the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
3
2
0
Order By: Relevance
“…As can be seen, and this was also noted by Wang et al [49], the Zukauskas and Ulinskas [50] correlation underestimates the pressure drop. Wang et al [49] presented a correction factor, but this factor was found to show very erratic variations in the considered range of , so it was not used.…”
Section: Test Set-up Benchmarksupporting
confidence: 79%
See 1 more Smart Citation
“…As can be seen, and this was also noted by Wang et al [49], the Zukauskas and Ulinskas [50] correlation underestimates the pressure drop. Wang et al [49] presented a correction factor, but this factor was found to show very erratic variations in the considered range of , so it was not used.…”
Section: Test Set-up Benchmarksupporting
confidence: 79%
“…Wang et al [49] presented a correction factor, but this factor was found to show very erratic variations in the considered range of , so it was not used. The good agreement between the experimental data and the predictions for = 3.57 (Fig 4B) should be considered coincidental, as the correlation is only valid for .…”
Section: Test Set-up Benchmarkmentioning
confidence: 99%
“…The results could be extrapolated to cover the lower pitch value but this would not help too much as the other two experimental sources tend to disagree within the range of pitch values considered therein. Overall, our results seem to be closer to those of T'Joen et al [186] at least for the reported data-points in that work. …”
Section: Numerical Detailssupporting
confidence: 91%
“…As another attempt to verify our numerical predictions, Figure 71 is presented to compare our simulation results (averaged over all velocities) for pressure drop with those available in the literature for single row banks of tubes. Interestingly, our results for the widest pitch considered here perfectly agree with experimental data from [186,187]; but the densest case considered in our work has not been investigated in the aforementioned papers. The results could be extrapolated to cover the lower pitch value but this would not help too much as the other two experimental sources tend to disagree within the range of pitch values considered therein.…”
Section: Numerical Detailssupporting
confidence: 89%
See 1 more Smart Citation